A revised teaching assistant-led extracurricular physical activity programme for 8- to 10-year-olds: the Action 3:30R feasibility cluster RCT - Russell Jago; Byron Tibbitts; Alice Porter; Emily Sanderson; Emma Bird; Jane E Powell; Chris Metcalfe; Simon J Sebire (NIHR Journals Library, 2019)
Background: Many children do not meet the recommended guidelines for physical activity. The after-school period may be a critical time for children to participate in physical activity. Teaching assistants are important within the school system and could be trained to deliver after-school physical activity programmes. Our previous work showed that a teaching assistant-led after-school physical activity intervention held promise. Objectives: To examine the feasibility, evidence of promise and cost of Action 3:30R, a revised after-school physical activity intervention. Design: A cluster-randomised feasibility study, including process and economic evaluations. Setting: The setting was 12 primary schools in south-west England. Participants: The participants were Year 4 and 5 children (aged 8-10 years). Intervention: Two teaching assistants from each intervention school attended a 25-hour (5-day) training course focused on how to deliver an after-school physical activity programme. As Action 3:30 is grounded in self-determination theory, the training focused on promoting children's autonomy, belonging and competence. Teaching assistants received resources to aid them in delivering a 60-minute after-school physical activity programme twice per week for 15 weeks (i.e. 30 sessions). Main outcome measures: Measures focused on feasibility outcomes and evidence of promise. Feasibility measures included the recruitment of schools and pupils and the attendance at the after-school programme. Evidence of promise was measured by comparing accelerometer-determined minutes of moderate to vigorous physical activity between the arms at follow-up. Process evaluation measures were conducted using the RE-AIM (Reach, Effectiveness, Adoption, Implementation, Maintenance) framework. The cost of delivery was also assessed. Results: Twelve primary schools were recruited and 41% of eligible pupils consented, 49% of whom were girls. Schools were randomised after baseline measures: six to the intervention arm (n = 170 pupils) and six to the control arm (n = 165 pupils). Two schools allocated to the intervention arm withdrew from the study before the start of the intervention, leaving 111 pupils in the intervention arm. The intervention training was well attended and positively received; eight out of nine teaching assistants attended 100% of the sessions. Action 3:30R clubs were well attended; 74% of pupils attended at least 50% of the 30 sessions. Mean weekday moderate to vigorous physical activity did not differ between the arms at follow-up (-0.5 minutes, 95% confidence interval -4.57 to 3.57 minutes). The process evaluation revealed that Action 3:30R was received positively by pupils, teaching assistants and key contacts in intervention schools. Pupils enjoyed Action 3:30R, and teaching assistants and pupils perceived the teaching style to be autonomy-supportive. Economic evaluation showed that Action 3:30R is inexpensive; the estimated cost of the programme after 1 year was £1.64 per pupil per session. Limitations: A reason for withdrawing was given by one school but not by the other. The reason given was an inability to release staff for training. Conclusions: Action 3:30R is a low-cost, feasible after-school programme that engages a range of pupils and offers continuing professional development to teaching assistants. However, Action 3:30R does not show evidence of promise in increasing levels of moderate to vigorous physical activity and does not warrant a trial evaluation. Future work: Future research should focus on improving the quality of current after-school provision in primary schools to increase physical activity. Trial registration: Current Controlled Trials ISRCTN34001941. Funding: This project was funded by the National Institute for Health Research (NIHR) Public Health Research programme and will be published in full in Public Health Research; Vol. 7, No. 19. See the NIHR Journals Library website for further project information.